Understanding Arranged Marriage: An Unbiased Analysis of a Traditional Marital Institution. (7th August 2021) - Tahir, Naema N
Abstract: This research asks one simple question, a question many studies on the arranged marriage omit to ask, namely "What exactly is the arranged marriage?" Author Naema Tahir, born and bred in the arranged marriage culture, but educated in the free-choice marriage culture, argues that much literature on the arranged marriage fails to offer full exploration of this traditional marital system. Instead, the arranged marriage is often analysed through the lens of the modern free choice marriage system. However, this is not a neutral lens. It considers the free choice marriage to be the ideal. As a result, the arranged marriage is perceived to be a "marriage of shortcomings", one that fails to meet the standards of the free-choice marriage system. The author encourages readers to break this frame and offers a neutral perspective on this traditional marital system practised by billions around the world. Readers are invited to an in-depth and rigorous analysis of the foundations upon which the arranged marriage system rests. While this analysis zooms in on the case study of one particular focus group, the British Pakistani diaspora, it reveals broad insights into the arranged marriage system in general. This analysis highlights and critically examines social principles fundamental to the arranged marriage system and which are much misunderstood, such as hierarchy, patriarchy, collectivism, group loyalty and the role of parental and individual marital consent. The author argues that it is vital to first understand the traditional structures of the arranged marriage, before one can understand modernizing tendencies the arranged marriage system is currently undergoing. As such, this study hugely contributes to an unbiased understanding of the arranged marriage and changing arranged marriage patterns and is a valuable reading for those interested in marriage, marital systems and the future thereof.